1996
DOI: 10.1182/blood.v88.8.3010.bloodjournal8883010
|View full text |Cite
|
Sign up to set email alerts
|

P-selectin glycoprotein ligand-1 is broadly expressed in cells of myeloid, lymphoid, and dendritic lineage and in some nonhematopoietic cells

Abstract: P-selectin glycoprotein ligand-1 (PSGL-1) is a muclin-like glycoportein ligand for P- and E-selectin on myeloid cells and a subset of lymphocytes. We used flow cytometry and immunohistochemistry to examine expression of PSGL-1 on minor leukocyte populations, differentiating hematopoletic cells, and nonhematopoietic tissues using two monoclonal antibodies to distinct protein epitopes on PSGL-1. In the bone marrow, PSGL-1 was expressed on myeloid cells from the myeloblast stage to the segmented neutrophil, but w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
105
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(113 citation statements)
references
References 34 publications
4
105
0
Order By: Relevance
“…In contrast to the ubiquitous expression of SCARB2 in somatic cells, PSGL-1 is restrictedly expressed in myeloid, lymphoid, and dendritic cells and serves as a common ligand for P-, L-, or Eselectin in platelets, leukocytes, or endothelium cells. It plays a role in leukocyte and inflammatory cell infiltration in inflammatory tissues (14,15). P-selectin glycoprotein ligand-1 has been identified as one of the receptors to which EV71 binds when it infects myeloid, lymphoid, and dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the ubiquitous expression of SCARB2 in somatic cells, PSGL-1 is restrictedly expressed in myeloid, lymphoid, and dendritic cells and serves as a common ligand for P-, L-, or Eselectin in platelets, leukocytes, or endothelium cells. It plays a role in leukocyte and inflammatory cell infiltration in inflammatory tissues (14,15). P-selectin glycoprotein ligand-1 has been identified as one of the receptors to which EV71 binds when it infects myeloid, lymphoid, and dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that hSCARB2 expression can enable normally unsusceptible cell lines to support EV71 propagation and develop cytopathic effects (8). P-selectin glycoprotein ligand-1 is a sialomucin membrane protein restrictively expressed in leukocytes, dendritic cells, tissue macrophages (those in the liver, lung, bowel, and Langerhans cells in the skin), and progenitor myeloid cells (14). It plays a role in the binding of leukocytes to endothelial cells and platelets and in the early stages of inflammation (14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SCARB2 is a type III double-transmembrane protein primarily located in endosomes, although surface expression of SCARB2 has also been demonstrated [17]. The second EV71 receptor, human P-selectin glycoprotein ligand-1 (PSGL-1/ CD162), is a sialomucin membrane protein expressed mainly in leukocytes, including dendritic cells and macrophages [18]. PSGL-1 was postulated to facilitate the viremic phase of EV71 by enabling replication in circulating leukocytes [19].…”
Section: Inhibitors Of Virus Attachment Entry and Uncoating Ev71 Recmentioning
confidence: 99%
“…PSGL-1 has binding ability to both L -selectin and E-selectin [21,22], but it is the main highaffinity specific ligand for P-selectin [18]. PSGL-1 is distributed on various cell types such as B cells, T cells ( g / d subset), residential and circulating dendritic cells, CD34 + stem cells and various myeloid cells from the bone marrow show a variable level of expression [23][24][25]. The binding between PSGL-1 and the selectins has been disrupted by the use of antibodies (Ab) raised against the specific selectins or to the ligand [18,21,23,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%